A multidisciplinary analytical framework to delineate spawning areas and quantify larval dispersal in coastal fish. (October 2019) - Legrand, T.; Di Franco, A.; Ser-Giacomi, E.; Caló, A.; Rossi, V.
Abstract: Assessing larval dispersal is essential to understand the structure and dynamics of marine populations. However, knowledge about early-life dispersal is sparse, and so is our understanding of the spawning process, perhaps the most obscure component of biphasic life cycles. Indeed, poorly known species-specific spawning modality and species-specific early-life traits, as well as the high spatio-temporal variability of the oceanic circulation experienced during larval drift, hamper our ability to appraise the realized connectivity of coastal fishes. Here, we propose an analytical framework which combines Lagrangian modelling, network theory, otolith analyses and biogeographical information to pinpoint and characterize larval sources which are then grouped into discrete spawning areas. Such well-delineated larval sources allow improving the quantitative evaluations of both dispersal scales and connectivity patterns. To illustrate its added value, our approach is applied to two case-studies focusing on Diplodus sargus and Diplodus vulgaris in the Adriatic sea. We evidence robust correlations between otolith geochemistry and modelled spawning areas to assess their relative importance for the larval replenishment of the Apulian coast. Our results show that, contrary to D. sargus, D. vulgaris larvae originate from both eastern and western Adriatic shorelines. Our findings also suggest that dispersal distances and dispersal surfaces scale differently with the pelagic larval duration. Furthermore, 30.8% of D. sargus larvae and 23.6% of D. vulgaris larvae of the Apulian populations originate from Marine protected area (MPA), exemplifying larval export from MPAs to surrounding unprotected areas. This flexible multidisciplinary framework, which can be adjusted to any coastal fish and oceanic system, exploits the explanatory power of a dispersal model, fine-tuned and backed-up by observations, to provide more reliable scientific basis for the management and conservation of marine ecosystems. Highlights: Integration of modelling, otolith and habitat data to assess coastal fish connectivity. Dispersal distances and surfaces scale differently with Pelagic Larval Duration. Fitting particle model with otolith geochemistry to evaluate spawning areas. Tremiti MPA is the largest larval source for D. sargus/vulgaris along Apulian Coast.